Seedborne diseases and their control - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Seedborne diseases and their control: principles and practice by R B Maude 1995 288pp price UKL £40.00 ISBN 0 85198 922 5